Efek Mediasi Financial Distress Dalam Hubungan Antara Profitabilitas dan Likuiditas Terhadap Firm Value (Studi Pada Perusahaan Manufaktur di Indonesia) - Melinda Dewi; Gabriella Foanto; Yulius Jogi Christiawan (Business Accounting Review, 2021)
Good company conditions will attract investors to invest, profitability and liquidity are important things in investor assessment. The higher profitability and liquidity value will reduce the possibility of a company to be in financial distress. This research aims to examine the mediating effect of Financial Distress in the relationship between Profitability and Liquidity to Firm Value. The study was conducted on 170 manufacturing companies listed on the IDX for the year 2016-2020. The data were analyzed using Partial Least Square (PLS) statistical analysis. The results show that there is perfect mediation in the relationship between Profitability and Firm Value through financial distress, as well as Liquidity as the independent variable. The main finding of this study is that Profitability and Liquidity have no direct effect on Firm Value, but have an indirect effect through Financial Distress. In accordance with signal theory, information related to financial situations that are free from Financial Distress can provide a positive signal for investors to invest so that Firm Value will increase. This research contributes to the firm who wants to maximize their Firm Value, also to the literature that are related to the mediating role of Financial Distress in predicting the effect of Profitability and Liquidity on increasing Firm Value.